2020
DOI: 10.1016/j.wasman.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking and optimising post-consumer packaging waste: A sentiment analysis of consumers’ perceptions towards the introduction of a deposit refund scheme in Scotland

Abstract: Highlights Online platforms are now an effective tool for marketing and policy development. Consumers’ emotions and opinions are important for interventions to be effective. Clarity about DRS including its operations is required to enhance participation. A UK-wide scheme with similar operations and structure should be introduced. DRS may not contribute to sustainability rather it might increase pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…For example, when a deposit refund system was introduced in Scotland, researchers have suggested that it would require a nationwide system similar in function and structure. If consumers' information and opinions about the deposit return system are contradictory, the system and its relevance are questioned (Oke et al 2020). For example, in Finland the deposit refunding system emphasizes the importance of paying attention to the requirements for a deposit, such as the cost of the deposit, how the deposit is financed, and how the disposal of plastic packaging purchased abroad should be treated (see e.g., Saario et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when a deposit refund system was introduced in Scotland, researchers have suggested that it would require a nationwide system similar in function and structure. If consumers' information and opinions about the deposit return system are contradictory, the system and its relevance are questioned (Oke et al 2020). For example, in Finland the deposit refunding system emphasizes the importance of paying attention to the requirements for a deposit, such as the cost of the deposit, how the deposit is financed, and how the disposal of plastic packaging purchased abroad should be treated (see e.g., Saario et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Such a program is the environmental responsibility of businesses and companies to ensure that waste is disposed of appropriately. Deposit-refund schemes have shown to increase the rate of solid waste recovery and recycling rates (once recycling schemes are in place) (Linderhof et al, 2019;Oke et al, 2020;Schneider et al, 2021). Thus, monetary deposits placed on retail price of engine oil bottles can encourage return and significantly reduce the amount of empty engine oil bottles found littering the coastline and bays.…”
Section: Figurementioning
confidence: 99%
“…, 2019). On the contrary, policy and market-based interventions, informed by research findings, provide a roadmap for designing and implementing pro-environmental initiatives, such as deposit return schemes (Oke et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%